Real-world data on the abuse potential of medications for the treatment of insomnia: a disproportionality analysis of the FAERS database - Saskin, Paul; McCall, William V.; Neubauer, David N.; Crucitti, Antonio; Perry, Bradford; Luyet, Pierre Philippe; Jaziri, Riphed; Vaillant, Cedric (Frontiers in Pharmacology, 2026)
BackgroundInsomnia disorder is a chronic medical condition estimated to affect 12% of adults. The potential for abuse of hypnotics often contributes to physician reluctance to prescribe medications to treat insomnia as a chronic condition. This study examined the real-world abuse potential of approved and off-label medications used to treat insomnia, employing data from the FDA Adverse Event Reporting System (FAERS) database.MethodsData from 1 January 2014 to 31 March 2024 were retrieved. Drugs of interest included Schedule IV drugs (benzodiazepines, Z-drugs, dual orexin receptor antagonists [DORAs]) and non-scheduled drugs (trazodone, doxepin, ramelteon). Relevant reported adverse events denoting drug abuse were identified if they contained an event with any preferred terms from the SMQ Drug abuse, dependence, and withdrawal (MedDRA v26.1), with cases of overdose due to suicide attempts excluded. The reporting odds ratios (ROR) and proportional reporting ratios (PRR) were used as disproportionality measures.ResultsRates of adverse event cases of abuse, dependence, and withdrawal retrieved were highest for benzodiazepines approved for any indication, followed by benzodiazepines approved for insomnia, trazodone, doxepin, Z-drugs, ramelteon, and DORAs. DORAs were associated with a low ROR value relative to Z-drugs (ROR = 0.150; 95% CI [0.131, 0.171]) and to trazodone (ROR = 0.092; 95% CI [0.081, 0.105]). Similar results were obtained using the PRR. The DORA class had the lowest rates of adverse event denoting drug abuse, even lower than the unscheduled drugs ramelteon and doxepin, which are known not to be prone to abuse or dependence. Furthermore, the DORA class had significantly lower odds of reporting for adverse events denoting drug abuse when compared with zolpidem or the unscheduled medication trazodone.ConclusionThis study identified significantly fewer reported cases of real-world abuse, misuse, overdose, and other safety risks for DORAs compared with the unscheduled drug trazodone and scheduled Z-drugs. This suggests that categorization of DORAs as Schedule IV drugs may overstate their abuse potential.